Presence of herpesviruses, parvoviruses, and polyomaviruses in sinonasal lymphoma - Jauhiainen, Maria K. (Springer Nature, 2025)
Purpose: Sinonasal lymphoma (SL) is a rare lymphatic neoplasm of the nasal cavities, paranasal sinuses and nasopharynx. Whereas some risk factors for SL subtypes have been identified, their aetiology is unknown. Along with other predisposing factors, the viral association of lymphomas, such as Epstein-Barr virus (EBV) and Burkitt and Hodgkin lymphomas, is well-established. Modern molecular biology techniques have enabled the discovery of novel human viruses, exemplified by the protoparvovirus cutavirus (CuV), associated with cutaneous T-cell lymphoma. These findings, and the anatomical location of the sinonasal tract with its rich microbiome and infectious agents, justify in-depth studies among SL.
Methods: We analysed the presence of 20 viruses of Orthoherpesviridae, Parvoviridae, and Polyomaviridae by qPCR in 24 SL tumours. We performed RNAscope in situ hybridisation (RISH) to localize the viruses. Parvovirus-specific IgG was analysed by enzyme immunoassay and targeted next-generation sequencing (NGS) was applied to detect CuV in plasma.
Results: We detected viral DNA in 15/24 (63%) tumours; nine of EBV, six of human herpesvirus (HHV) -7, four each of HHV-6B and parvovirus B19, two of cytomegalovirus, and one each of CuV and Merkel-cell polyomavirus. We found tumours with up to four viruses per tumour, and localized CuV and EBV DNAs by RISH. Two of the ten plasma samples exhibited CuV IgG, and one plasma sample demonstrated CuV viremia by NGS.
Conclusion: Viruses were frequent findings in SL. The EBV detection rate was high in diffuse large B-cell lymphoma, and co-detections with other viruses were prevalent.